THE CORRELATION AMONG READING HABIT, READING STRATEGY, AND STUDENTS’ READING COMPREHENSION OF TRIDINANTI UNIVERSITY PALEMBANG - Wiwik Septiani; Gaya Tridinanti (Jurnal Didascein Bahasa, 2018)
The objectives of this study were to find out whether or not the students’ reading habit and students’ reading strategy correlated significantly with their reading comprehension and to find out whether or not students’ reading strategy correlated significantly with their reading comprehension. The method of this research used quantitative method in correlation research. The sample of the study was seventeen of third semester students of English Education Study Program of Tridinanti University Palembang. The data were collected by administering reading test and gives two questionnaires; reading habit questionnaires and reading strategy questionnaires. The data were analyzed by using descriptive and correlational analyses. There were two results found: First, the students’ reading  habit had no significant correlation with their reading comprehension. It was found that correlation coeficient  level between reading habit and reading comprehension was (-0.099) with the sig. value was higher than 0.05 (0.705). Second, the correlation coeficient level between students’ reading strategy and reading comprehension was not correlated (-0.451) with the  sig. value higher than 0.05 (0.069).Keywords:  reading habit, reading strategy, reading comprehension.